The University of Oporto and the Process of Urban Change: An Ambiguous Relationship - Isabel Breda Vázquez (2008)
This chapter analyses the role of the university as a promoter of urban development in the city of Oporto, in Portugal. The argument is developed as follows: i) the university is an important operator in urban change; ii) however, the relationship established between the universitys real estate policy, the territory itself and urban policies is ambiguous and marked by a gulf which exists between the universitys strategies and the specific problems of the urban context to which it belongs; iii) any interpretation of this ambiguity requires an analysis based on institutions, or on institutional relationships and capacities. This argument emphasizes the ambiguous and contingent role played by the university in the process of urban development and recognizes that this role is not always explicitly incorporated into the strategy of the main urban agents, such as the local authority or the university itself.